Analisis Pengaruh Kualitas Layanan Terhadap Loyalitas Pelanggan Toko Ritel Modern di Nabire Dimediasi Kepuasan Pelanggan - Irawan, Immanuel Candra; Wabiser, Krista (Politeknik Negeri Ambon, 2025)
The competition in the modern retail business is increasingly fierce, marked by the growing number of modern retail outlets. Building customer loyalty is crucial to gaining a competitive advantage. This research aims to analyze the factors influencing customer loyalty in modern retail stores in Nabire, Central Papua Province. The sample of 198 respondents was collected using purposive sampling. The data was processed using the PLS-SEM method with SmartPLS version 3. The research results show that 1) service quality significantly influences customer satisfaction, 2) service quality significantly influences customer loyalty, 3) customer satisfaction significantly influences customer loyalty, and 4) service quality significantly influences customer loyalty through customer satisfaction.